2007
DOI: 10.1016/j.ydbio.2007.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Three male germline-specific aldolase A isozymes are generated by alternative splicing and retrotransposition

Abstract: Enzymes in the glycolytic pathway of mammalian sperm are modified extensively and are localized in the flagellum, where several are tightly bound to the fibrous sheath. This study provides the first evidence for three novel aldolase isozymes in mouse sperm, two encoded by Aldoart1 and Aldoart2 retrogenes on different chromosomes and another by Aldoa_v2, a splice variant of Aldoa. Phylogenetic analyses and comparative genomics indicate that the retrogenes and splice variant have remained functional and have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 85 publications
5
58
0
2
Order By: Relevance
“…Similar to that analysis, we have found that in mouse sperm, tubulin, VDAC, PDH E1 β chain, glutathione S-transferase, NADH dehydrogenase (ubiquinone) Fe-S protein 6, acrosin binding protein precursor, proteasome subunit alpha type 6b, and cytochrome b-c1 complex are phosphorylated in tyrosine residues. Interestingly, among the proteins phosphorylated on tyrosine residues we have identified two recently described testis-specific aldolases (Vemuganti et al, 2007). Aldolase is the fourth enzyme of glycolysis; in mouse sperm, this metabolic process is the main pathway for ATP production as was demonstrated using null mutants of other glycolytic enzymes (Miki et al, 2004).…”
Section: Characterization Of Proteins That Undergo Tyrosine Phosphorymentioning
confidence: 90%
“…Similar to that analysis, we have found that in mouse sperm, tubulin, VDAC, PDH E1 β chain, glutathione S-transferase, NADH dehydrogenase (ubiquinone) Fe-S protein 6, acrosin binding protein precursor, proteasome subunit alpha type 6b, and cytochrome b-c1 complex are phosphorylated in tyrosine residues. Interestingly, among the proteins phosphorylated on tyrosine residues we have identified two recently described testis-specific aldolases (Vemuganti et al, 2007). Aldolase is the fourth enzyme of glycolysis; in mouse sperm, this metabolic process is the main pathway for ATP production as was demonstrated using null mutants of other glycolytic enzymes (Miki et al, 2004).…”
Section: Characterization Of Proteins That Undergo Tyrosine Phosphorymentioning
confidence: 90%
“…Glycolysis can therefore serve as supplier of ATP to the flagellar dynein ATPase for motility in mouse sperm; evidence that this is the case is presented below. The concept that the sperm-specific enzyme isoforms of the Embden-Meyerhof pathway are so constructed as to bind to this scaffold remains to be fully validated, but the number of these isoforms is impressive: phosphoglycerate kinase-2 (PGK2), GPI, phosphofructose kinase-1 (PFK1), and EN (see Vemuganti et al, 2007, for listing and references), and aldolase. The recent finding of Vemuganti et al (2007) that three sperm-specific isoforms of aldolase are localized in the mouse sperm flagellum, of which two have N-terminal extensions not found in the others.…”
Section: Glycolysis: Sugar As Friendmentioning
confidence: 99%
“…The concept that the sperm-specific enzyme isoforms of the Embden-Meyerhof pathway are so constructed as to bind to this scaffold remains to be fully validated, but the number of these isoforms is impressive: phosphoglycerate kinase-2 (PGK2), GPI, phosphofructose kinase-1 (PFK1), and EN (see Vemuganti et al, 2007, for listing and references), and aldolase. The recent finding of Vemuganti et al (2007) that three sperm-specific isoforms of aldolase are localized in the mouse sperm flagellum, of which two have N-terminal extensions not found in the others. These N-terminal extensions are tempting candidates for anchor sequences to the fibrous sheath of the flagellum, but have not yet won experimental confirmation.…”
Section: Glycolysis: Sugar As Friendmentioning
confidence: 99%
“…Aldolase B is highly expressed in both kidney and liver whereas aldolase C is found mainly in the nervous system, but has been also identified in bovine spermatozoa (Fiedler et al 2008). In addition, three novel aldolase A isoenzymes are expressed in mouse spermatozoa (Vemuganti et al 2007).…”
Section: Introductionmentioning
confidence: 99%